Community leisure and recreation planning - Marriott, Ken (Abingdon, Oxon ; New York, NY : Routledge, 2021)
Community Leisure and Recreation Planning offers an up-to-date, evidence-based approach to planning community leisure and recreation facilities, programs and services. It introduces readers to key theory and best practice in the planning of effective leisure and recreation projects. The book defines planning, leisure, recreation and other key concepts and explains why a thorough planning process is essential to achieving effective outcomes. It presents a comprehensive, integrative four phase model for undertaking leisure and recreation planning, including: pre-planning, planning research, preparing a plan, and implementing, monitoring and evaluating the outputs and outcomes of a plan. It provides a conceptual rationale for each component of the planning process, a detailed explanation of the tools and techniques that can be used, and extensive examples and international case study materials to demonstrate their use. The principles and techniques explained in the book are applicable at a range of community levels from small individual sites to regions, states and even countries. This is an essential course text for all leisure and recreation courses, and invaluable reading for academics, practitioners, stakeholders and students working in leisure and recreation planning, events, culture and sport.
OCLC-licensed vendor bibliographic record.
Keywords: Recreation -- Planning; Leisure -- Planning; Recreation -- Management; SPORTS & RECREATION / General